Integrating tobacco cessation into routine dental practice: protocol for a qualitative study - Shah, Rachana (BMJ Open, 2019)
INTRODUCTION: Combined efforts to encompass different aspects of tobacco control have been in place for some time. Despite the recognition of the need to offer support to tobacco users to quit tobacco use, such support remains highly inadequate in India. However, little is known about the practice of oral health professionals (OHP) and the experiences and expectations of dental patients in the context of tobacco cessation (TC) services. In this article, we describe the protocol of a doctoral research project that explores OHPs and their patients in an Indian city. The aims are (A) to understand the functioning of the oral healthcare system towards TC and what changes to it will be needed to benefit TC and (B) to capture the views of dental patients on TC services provided by OHPs. METHODS AND ANALYSIS: A cross-sectional qualitative study based on individual interviews with OHPs and dental patients will be carried out in the city of Ahmedabad, Gujarat, India. The OHP will be purposively selected from two major organisation types: (1) single-doctor dental clinics and (2) dental hospital attached to teaching institutions. The sample population will be divided into two subgroups: general OHP (dentists practising general dentistry irrespective of their qualification) and prosthodontists (dentists with a specialisation in prosthodontics). We will sample dental patients through convenient sampling from a public teaching hospital and select private dental care facilities. The sampling of OHPs and dental patients will continue until we reach data saturation. Interviews will be audio recorded, transcribed verbatim and coded by hand. The interview transcript will subsequently be analysed using thematic content analysis. ETHICS AND DISSEMINATION: The study received ethical approval from the Institutional Ethical Committee of the Government Dental College and Hospital, Ahmedabad. The findings will be disseminated through conference presentations, peer-reviewed publications and to the study participants.